Efficacy and safety of a fixed‐dose combination of ibuprofen and caffeine in the management of moderate to severe dental pain after third molar extraction - Weiser, T. (Eur J Pain, 2017)
BACKGROUND: Ibuprofen is an effective analgesic treatment with a ceiling effect at doses above 400 mg. This study compared the combination of ibuprofen 400 mg and caffeine 100 mg with ibuprofen 400 mg monotherapy, caffeine and placebo in the analgesic treatment of moderate to severe acute dental pain following third molar extraction. METHODS: Phase III, active‐/placebo‐controlled, double‐blind, single‐centre, two‐stage, parallel‐group study in adult patients with at least moderate baseline pain intensity. Primary endpoint was defined as the time‐weighted sum of pain relief and pain intensity difference over 8 h (SPRID0–8 h), secondary endpoints included duration of pain relief, time to meaningful pain relief and more. RESULTS: N = 748 patients were enrolled and N = 562 treated. Mean baseline pain intensity was 7.7 on a 0–10 numerical rating scale. Analysis of SPRID0–8 h demonstrated superior analgesic effects for a single dose of ibuprofen/caffeine versus ibuprofen, caffeine and placebo over 8 h, rescue medication in this stage was requested by more patients on ibuprofen (32.5%) than on ibuprofen/caffeine (16.0%). Median time to meaningful pain relief was shorter for ibuprofen/caffeine (1.13 h) compared with ibuprofen (1.78 h; p = 0.0001). More patients on ibuprofen/caffeine than on ibuprofen reported meaningful pain relief. Adverse events were infrequent and mostly mild or moderate across treatment groups. Tolerability was rated as ‘very good’ or ‘excellent’ by most patients in both treatment groups. CONCLUSION: This study demonstrated clinically relevant superiority of ibuprofen/caffeine over monotherapy with ibuprofen in patients with acute dental pain. All treatments were well tolerated. SIGNIFICANCE: This trial showed superior efficacy of 400/100 mg ibuprofen/caffeine, compared to 400 mg ibuprofen alone, for treating acute pain, reflecting that caffeine is an effective analgesic adjuvant. Data on efficacy of 400 mg ibuprofen combined with caffeine for the treatment of acute pain were not available yet.